Research on designers’ behavioral intention toward Artificial Intelligence-Aided Design: integrating the Theory of Planned Behavior and the Technology Acceptance Model - Jiao, Jinchuan; Cao, Xiangnan (Frontiers in Psychology, 2024)
Artificial Intelligence-Aided Design (AIAD) has numerous advantages and tremendous benefits for designers. However, not all designers are keen to integrate AIAD into their workflow, and their intention to use AIAD remains a research gap. This study explores designers’ adoption of AIAD, utilizing the Theory of Planned Behavior (TPB) and the Technology Acceptance Model (TAM). Drawing on extant literature, we proposed a research model and tested it using data from 392 Chinese designers. The results indicate that in terms of AIAD, (a) designers’ attitudes toward AIAD (b = 0.259, p < 0.001), subjective norms (b = 0.363, p < 0.001), and perceived behavioral control (b = 0.556, p < 0.001) have significant and positive impacts on their intention to use AIAD; (b) perceived usefulness of AIAD (b = 0.910, p < 0.001) has a positive and significant correlation with attitudes toward AIAD while perceived ease of use (b = −0.126, p < 0.05) exerts no significant impact on attitudes; (c) the knowledge level of designers (b = −0.149, p < 0.01) has a negative moderating effect on the impact of attitudes toward AIAD on the intention to use them. The present research then discusses its practical significance.